Effects of perspective-taking training based on relational frame theory for cognitive empathy and emotional empathy: Differences in perspective-taking according to various theoretical approaches - Yasuhiro Ooshima; Takashi Mitamura (PLoS ONE, 2025)
Perspective-taking has garnered considerable attention across various psychological domains and is often conceptualized as cognitive empathy within the organizational model of empathy. Relational frame theory, a theoretical framework elucidating human behavior and language, addresses perspective-taking and offers corresponding training protocols. However, previous studies have not examined the relationship between training and perspective-taking, defined as cognitive empathy in the organizational model of empathy. This study investigated the impact of perspective-taking training rooted in the relational frame theory on perspective-taking, as conceptualized by the organizational model of empathy. To this end, 43 participants underwent a training regimen and completed pre- and post-training assessments using questionnaires that measure organizational empathy. The post-training scores for the subscales measuring cognitive empathy increased significantly (p = 0.031); however, The increase in the score remained significant trend after adjusting for training performance. The scores for some subscales of emotional empathy also increased after training. The limitations of this study include a bias in the sample and discrepancies in the results between scales measuring the same concept. Nonetheless, these results provide scope for debate regarding the impact of perspective-taking training under relational frame theory on perspective-taking within the organizational model of empathy. While considering the limitations of the obtained results, this study discusses the relationship between perspective taking based on relational frame theory and the organizational model of empathy, including emotional empathy.